The effect of disability and depression on cognitive function and screening factors. (November 2017) - Chen, Chun-Min; Liu, Li-Fan
Highlights: Long-term Care Policy 2.0 in Taiwan has launched since 2016 and tried to add care for people with mild cognitive impairment (MCI) and Dementia. The LTC 2.0 policy includes the aim to early detect people with cognitive impairment in the community to prevent from further deterioration to Dementia. It has been well documented that the relationship between functional limitations and cognitive impairments. Although exist some measurements of Dementia and cognitive impairments, it is not easy for family caregivers or frontier care workers in the community to detect early Dementia. Since disability is more visible than mental health in practice, it could be useful to include both disability and depression to detect cognitive impairment. This is the first study to examine the interrelationship between disability, depression and cognitive impairment by using path analysis for the community-dwellings aged 65 and over in Taiwan. In the study, it was found that disability and depression may independently or jointly contribute to the cognitive impairment. Disability may also mediate the relationship between depression and cognitive impairment. Since geriatric conditions were associated with higher cognitive impairment among those who are female and very old, early assessment could be arranged to this high-risk subgroup to reduce the incidence of future Dementia. Abstract: Introduction: There is increasing evidence that subtle losses in cognitive function may be symptomatic of a transition to early dementia. The objectives of this study were to: 1) test the effect of depressive symptoms and/or disability on cognitive impairment, 2) explore the interaction between depression and disability and the association with cognitive impairment, and 3) evaluate risk factors of health assessment to discriminate between elderly people with or without cognitive impairment. Material and methods: The subjects were the community-dwellings aged 65 years and over who live in the sample city of southern Taiwan. 2734 persons were recruited by random sampling in the community, and the data was collected with face to face interviews by the training interviewers. Results: The effect of disability on cognitive impairment is stronger than the effect in depression. It also implies the possibility that disability may mediate the association between depression and cognitive impairment. Screening for risk factors of cognitive impairment was defined in this study and may be feasible for general population. Conclusions: This study suggests that disability and depression assessments may serve as useful predictors of cognitive impairment. It is hoped that for elderly people, early assessment through screening factors could be arranged to this high-risk subgroup to reduce the risk of developing future dementia. Screening for functional disability and depressive symptoms would help to put management strategies in place that may reduce the associated cognition impairment burden.